Aortic valve replacement with biological prosthesis in patients aged 50–69 years. (1st December 2020) - Malvindi, Pietro Giorgio; Luthra, Suvitesh; Olevano, Carlo; Salem, Hamdy; Kowalewski, Mariusz; Ohri, Sunil
Abstract:  : OBJECTIVES: There is no consensus regarding the use of biological or mechanical prostheses in patients 50–69 years of age. Previous studies have reported a survival advantage with mechanical valves. Our goal was to compare the long-term survival of patients in the intermediate age groups of 50–59 and 60–69 years receiving mechanical or biological aortic valve prostheses. METHODS: We conducted a retrospective analysis of patients in the age groups 50–59 years ( n  = 329) and 60–69 years ( n  = 648) who had a first-time isolated aortic valve replacement between 2000 and 2019. Kaplan–Meier and competing risk analyses were performed to compare survival, incidence of aortic valve reoperation, haemorrhagic complications and thromboembolic events for mechanical versus biological prostheses. RESULTS: Patients aged 50–59 years with a biological prosthesis had a higher probability of aortic valve reintervention (26.3%, biological vs 2.6% mechanical; P  < 0.001 at 15 years). The incidence of haemorrhagic complications or thromboembolic events was similar in the 2 groups. Patients aged 60–69 years with a mechanical prosthesis had a higher risk of haemorrhagic complications (6.9%, biological vs 16.2%, mechanical; P  = 0.001 at 15 years). Biological prostheses had a higher overall probability of reintervention for valve dysfunction (20.9%, biological vs 4.8%, mechanical; P  = 0.024). In both age groups, there was no difference in long-term survival between patients receiving a biological or a mechanical prosthesis. CONCLUSIONS: There was no difference in long-term survival between mechanical and biological prostheses for both age groups. Mechanical prostheses had a higher risk of bleeding in the 60–69-year group whereas biological valves had higher overall reintervention probability without an impact on long-term survival. It may be safe to use biological valves based on lifestyle choices for patients in the 50–69-year age group.